2021
DOI: 10.1097/prs.0000000000008706
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Length of Stay for Microvascular Breast Reconstruction: An Evaluation of 10,465 Cases Using the American College of Surgeons National Surgical Quality Improvement Program Database

Abstract: he American Cancer Society estimates that there will be 276,480 new diagnoses of female breast cancer in 2020, an increase of 0.3 percent from 2019. 1 Although implant-based reconstructions following mastectomy are more common, the rate of tissue-based breast reconstruction has increased in recent years. 2,3 Relative to implant-based breast reconstruction, autologous breast reconstruction consumes more resources and requires longer inpatient admissions. Longer lengths of stay have been linked to greater

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…19 A group that performed a national analysis of breast free-flap reconstruction patients similarly noted a decrease in LOS from 4.47 to 3.90 days during the years of 2012 to 2018. 20 Meanwhile, our study, and the work of Jablonka et al 14 and Baltodano et al 17 support discharge on POD 2 without an increase in flap or patient complications. Jablonka et al 14 showed that the implementation of ERAS protocols could reduce LOS to as low as 2-3 days while maintaining a complication rate of 8.7% with a failure rate of 2.2%.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…19 A group that performed a national analysis of breast free-flap reconstruction patients similarly noted a decrease in LOS from 4.47 to 3.90 days during the years of 2012 to 2018. 20 Meanwhile, our study, and the work of Jablonka et al 14 and Baltodano et al 17 support discharge on POD 2 without an increase in flap or patient complications. Jablonka et al 14 showed that the implementation of ERAS protocols could reduce LOS to as low as 2-3 days while maintaining a complication rate of 8.7% with a failure rate of 2.2%.…”
Section: Discussionsupporting
confidence: 70%
“…The majority of articles that detail ERAS protocols have described successful discharge after DIEP breast free-flap reconstruction on POD 3, such as DelMauro et al 18 who reported average LOS as 3.26 ± 1.19 days and Bonde et al 19 who reported a significant reduction in LOS of 3.6 ± 0.85 from 4.7 ±1.04 days 19 . A group that performed a national analysis of breast free-flap reconstruction patients similarly noted a decrease in LOS from 4.47 to 3.90 days during the years of 2012 to 2018 20 . Meanwhile, our study, and the work of Jablonka et al 14 and Baltodano et al 17 support discharge on POD 2 without an increase in flap or patient complications.…”
Section: Discussionmentioning
confidence: 97%
“…The reduced LOS trend was also seen from the American College of Surgeons National Database, where LOS after unilateral reconstructions decreased from 4.47 days in 2012 to 3.9 days in 2018 [ 21 ]. In a single center cohort study from the Netherlands, ERAS reduced the LOS from 6.2 to 5 days [ 14 ].…”
Section: Discussionmentioning
confidence: 92%
“…Meanwhile, the absolute number of hospital days in the current study seems to be longer than that for microvascular breast reconstruction in the United States. According to Holoyda et al ( 22 ), the mean length of hospital stay in the U.S. was 3.90 days in 2018. However, a direct comparison of hospital stays between two countries with different healthcare systems is not appropriate.…”
Section: Discussionmentioning
confidence: 99%